The complexity of circulating HIV type 1strains in Oyo state, Nigeria (2007)
Multiple HIV-1 subtypes and circulating recombinant forms (CRFs) are known to circulate in west Africa. We undertook a survey of HIVs in Oyo state, in southwestern Nigeria. We analysed 71 samples from Ibadan the capital city, and 33 samples form Saki, 100 miles west of Ibadan. We sequenced part of the gag gene and the envelope C2V3 region from 102 and 89 samples, respectively. In the 87 samples for which both genes were sequenced, subtypes G and CRF02_AG were found in equal proportions (32.2%each). Other samples included CRF06_cpx(8.0%), subtype A (2.3%), C(1.1%), unclassified(1.1%), or discordant sequences suggesting the presence of a large number of recombinants involving CRF02_AG and/or subtype G(20.7%) or other subtypes(2.3%). The subtype/CRF designation was concordant in two gene fragments in the majority of samples evaluated. However, we observed difference in subtype distribution between the two locations with a predominance of subtypes G in Ibadan and CRF02 in Saki. This is first in-depth analysis of HIV variability at a state level in Nigeria. Our analysis revealed a significant level of viral heterogeneity and a geographical difference in subtype distribution, and demostrated that CRF02_AG does not account for the majority of circulating strains.